Vaccination of pregnant guinea pigs with aromatic dependent Salmonella typhimurium to protect their newborns: Yousif .A.A, Habasha.F.G,Khalifa. A.K. - A., Yousif A. (The Iraqi Journal of Veterinary Medicine, 2006)
Genetically altered stable non reverting aromatic dependent (aro)Salmonella typhimurium,strain SL1479 was administrated intramuscularly tohealthy pregnant guinea pigs as alive vaccine. Twenty one pregnant guinea pigswere divided into two groups, the first group (15 animals) was vaccinated twicewith 1ml containing 17 C.f.U /ml approximately fourth and second week preparturitionand the second group (6 animals) injected with 1ml trypticase soybroth (TSB) as a control group.Adverse reaction to vaccination were not observed in the pregnant guineapigs, which parturated normally. The vaccine induced humoral and cellularimmune response as measured by tube agglutination test and delayed typehypersensitivity(DTH)-skin test in the immunized dams and transfer of thisresponse to the newborns, which revealed a high titers ofO(somatic)&H(flagller) agglutination titers and positive delayed typehypersensitivity(DTH)- skin test.The newborn overcome the challenge with virulent Salmonellatyphimurium at 3,6 &8 weeks of age, compared with the controlnewborn which died. These results revealed the efficacy of theprenatal vaccination with aro Salmonella typhimurium to transfer thepassive immunity to the newborn.